PHYSICAL ACTIVITY, BODY MASS, BODY COMPOSITION AND THE LEVEL OF AEROBIC CAPACITY AMONG YOUNG, ADULT WOMEN AND MEN - Karol Görner; Tomasz Boraczyński; Jože Štihec (Sport Scientific And Practical Aspects, 2025)
Low level of physical activity is thought to be one of the main factors of many diseases development. Physical activity and aerobic capacity are very important elements of health. The aim of the study was to assess the relations between physical activity, body composition and level of aerobic capacity among young, adult women and men. The study involved 218 physiotherapy students (128 females and 90 males) and 380 physical education students (122 females and 258 males). The questionnaire was applied to assess their level of physical activity. Body mass was measured using Tanita BC 418 MA analyser. Height was measured using a Holtain stadiometer. Skinfold thicknesses were measured using a GPM caliper. Aerobic capacity was assessed indirectly taking into account the results of the PWC 170 test. The ANOVA analysis was used.The results of the study demonstrated that women and men being physical education students characterised a higher level of physical activity than physiotherapy students. Female students of physical education have a significantly lower fat content and a significantly higher level of aerobic capacity, compared to the students of physiotherapy. Male students of physical education have a significantly lower body mass, lower fat content, lower value of the BMI index, as well as a significantly higher level of aerobic capacity, compared to the students of physiotherapy. The results indicate that women and men who have an active lifestyle characterised normal body fat content, BMI index and a higher level of aerobic capacity.